2013
DOI: 10.1002/anie.201303705
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Insertion of Unactivated Alkenes into Silicon(II)–Tin Bonds

Abstract: The migratory insertion of alkenes is one of the most fundamental processes in organometallic chemistry and thus plays a crucial role in many catalytic processes, such as polymerization, [1] 1,2-addition reactions, [2,3] and Heck-type reactions. [4] In many cases, the insertion reaction is reversible, and a key step in catalysis is the formation of alkenes through a b-hydride elimination from alkyl transition-metal complexes.In the case of nonmetallic systems, the olefin-insertion reaction is long-known in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Similar alkyne insertion reactivity was later observed for a diborylstannylene [15]. A related ethylene insertion was observed previously in the Si-Sn bond of a stannylated silylene adduct [16], and later in the Si-Si bond of the stable acyclic silylene dipp(Me 3 Si)N-Si-Si(SiMe 3 ) 3 (dipp = 2,6-iPr 2 C 6 H 3 ) [17]. More recently, Sasamori, Tokitoh and co-workers reported the spectacular example of a digermyne acting as a main group catalyst for the cyclotrimerization of arylacetylenes.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar alkyne insertion reactivity was later observed for a diborylstannylene [15]. A related ethylene insertion was observed previously in the Si-Sn bond of a stannylated silylene adduct [16], and later in the Si-Si bond of the stable acyclic silylene dipp(Me 3 Si)N-Si-Si(SiMe 3 ) 3 (dipp = 2,6-iPr 2 C 6 H 3 ) [17]. More recently, Sasamori, Tokitoh and co-workers reported the spectacular example of a digermyne acting as a main group catalyst for the cyclotrimerization of arylacetylenes.…”
Section: Introductionsupporting
confidence: 84%
“…All hydrogen atoms omitted for clarity (bond lengths in Ả, angles in deg). Ge(1)-P(1) 2.3900 (16), Ge(1)-Ge(2) 2.4980(9), Ge(1)-Ge(3) 2.5114(9), Ge(2)-Cl(1) 2.2177 (15), Ge(2)-Cl(2) 2.2228 (15), Ge(2)-Si(1) 2.3966 (15), Ge(3)-Cl(3) 2.2149 (15), Ge(3)-Cl(4) 2.2397 (16), Ge(3)-Si(5) 2.4101 (18)…”
Section: Figurementioning
confidence: 99%
“…This low value may be due to local diamagnetic phenomena and 2 can actually be considered to be slightly antiaromatic . The Si1−P bond distances are only slightly longer than those observed for phosphine‐stabilized silylenes (2.31–2.35 Å), thus suggesting a strong coordination of the phosphine ligands on the Si IV atoms. Of particular interest, both isomers of 2 present exceptionally short Si1⋅⋅⋅Si1′ diagonal distances [ 2 a : 2.23502(17) Å, 2 b : 2.2303(10) Å], which are significantly shorter than those observed for tetramesityl‐1,3‐disiloxanes (2.31–2.39 Å), and are within the range expected for Si=Si bonds (2.15–2.23 Å) …”
Section: Methodsmentioning
confidence: 86%
“…[14] Nikonov et al reported on the reversible reaction of RAl and RAlH 2 , yielding the dialane R(H)AlÀAl(H)R. [15] Furthermore, alkynes reversibly react with Lapperts stannylene [(Me 3 Si) 2 CH] 2 Sn and with a digallane, [16,17] whereas the reversible, temperature-controlled binding and release of C 2 H 4 was observed in reactions with a distannyne and with Si II complexes. [18,19] Ragogna et al reported the reversible, photoinduced activation of P 4 by reaction with a Ge II compound. [20] In contrast, the formation of a fully reversible equilibrium between a low-valent main-group metal complex and the corresponding intermetallic complex is without precedent.…”
mentioning
confidence: 98%